The role of citizen journalism in strengthening the principle of freedom of expression and the formation of public opinion - Kirat, Saddam Hocine; Si Youcef, Baya (Journal of Human Sciences, 2022)
This study aims to know the role that citizen journalism plays in strengthening the principle of freedom of expression and the formation of public opinion, by opening the way for pluralism of opinions, highlighting the reality of censorship imposed on citizen journalist participation, the mechanisms for overcoming it, the factors that attract citizen journalism to the public, and how to arouse it to the attention of the media. The study reached a number of results, the most important of which is that citizen journalism, as a new media, enables members of the ordinary public to express their opinions, concerns and needs, and this increases their ability to make change in all fields and to form, shape and direct public opinion on a particular issue, and this is by employing the skills gained from practicing Citizen journalism and the recruitment of masses who are accustomed to receiving and following up on the contents and content produced and published by citizen journalists through social networks.